Effects of Ecballium Elaterium on Proinflammatory Cytokines in a Rat Model of Sepsis. (1st November 2016) - Arslan, Mehmet Serif; Basuguy, Erol; Ibiloglu, Ibrahim; Bozdemir, Eda; Zeytun, Hikmet; Sahin, Atalay; Kaplan, Ibrahim; Aydogdu, Bahattin; Otcu, Selcuk
ABSTRACT: Objective: Ecballium elaterium (EE) is a plant from Cucurbitaceae family. Its anti-inflammatory role in sepsis is not well understood. We investigated the effects of EE on serum levels of proinflammatory cytokines and further explored the mechanisms underlying histological changes in liver and ileum following EE administration in a polymicrobial sepsis model. Methods: Thirty rats were divided into three groups of 10 rats each. Rats were subjected to sham laparotomy plus normal saline administration (control group, CG), laparotomy with cecal ligation and puncture (CLP) (sepsis group, SG), and laparotomy with CLP plus 2.5 mg/kg EE administration (experimental group, EG). Twenty-four hours after laparotomy, animals underwent cardiac puncture, and blood was collected for interleukin 1 (IL-1), interleukin 6 (IL-6), and tumor necrosis factor alpha (TNF-α) assessment. Whole sections of liver and ileum tissues were collected for histologic examination. Results: The serum level of IL-6 was significantly lower in EG as compared to SG. Although IL-6 levels were shown a statistically significant ( p < 0.0001) decline to near control values, no significant changes were observed in serum levels of IL-1 and TNF-α after EE treatment. Histologic examination revealed statistically significant reduction in collagen formation ( p = 0.001) on serosal surface of ileum and hepatic venous congestion ( p = 0.040) in EG as compared to SG. Conclusion: EE might play a protective role in sepsis prevention and treatment by decreasing IL-6 production and reducing liver damage and may influence bacterial translocation by reinforcing intestinal barrier function.